Caracterização nutricional e de compostos bioativos do Jambolão (Syzygium cumini (L.) Skeels) - Figueiredo, Teresa de Avila Ribeiro de [UNIFESP] (2020)
Jambolão (Syzygium cumini (L.) Skeels) is an exotic fruit belonging to the Myrtaceae family, originally from tropical Asia. In Brazil, it is found in most states, with remarkable adaptation to coastal areas, which includes the city of Santos, located on the coast of São Paulo. Where, of course, there is a wide distribution of leafy trees, with bushes of exuberant beauty, abundant fruit production, in the summer until the fall of each year. The great amount of fruit fallen under the crowns and, above all, the strong purple color impregnated in the soil, aroused the interest of this research. Thus, in April, the ripe fruits of the 2018 and 2019 harvests were harvested. Some researchers reported the effects of using the stem bark, leaves, fruits and seeds of the jambolão, in the form of extracts and / or infusions applied in prevention and treatment of certain chronic non- communicable diseases. However, few experimental studies were carried out with the aim of characterizing the organic, mineral and bioactive content of this fruit species. Thus, this study aimed to characterize and compare the nutritional composition and bioactive compounds, in the edible portion, (pulp plus bark), of the local jambolan. Our results showed in the nutritional composition average levels of (81-86 g / 100g) of moisture; (0.4-0.5 g / 100g) protein; (1 g / 100g) for lipids; (0.30 g / 100g) of ash, (3.5 -5 g / 100g) of soluble fibers; (1.6-1.8g / 100g) of insoluble fibers and (2.1-2.4g / 100g) total fibers; with (3.9) pH; (1.4-2%) total soluble solids and (17-20%) Brix grade. Mineral composition containing: (10-16 mg / 100g) calcium, (22-24 mg / 100g) magnesium, (22-27mg / 100g) phosphorus, (115-126mg / 100g) potassium, (0.35 -0.37mg / 100g) iron, (1.2-1.8mg / 100g) sodium, (0.06-0.08mg / 100g) copper, (0.1mg / 100g) manganese and (0,5mg/100g) of zinc. By HPLC-PDA, the total of identified carotenoids was 90 ± 23 to 92 ± 11 g / 100 g of total carotenoid sample in the 2018 harvest and 83.2 ± 22 to 90.3 ± 13 g / 100 g sample of total carotenoids in the 2019 harvest; Within this total, two carotenoids stood out as majorities, the all-trans-lutein, with 40.07 ± 17 to 43.67 ± 32 g / 100g of sample in the 2018 harvest, and 48.94 ± 11 to 43.48 ± 32 g / 100g of sample in the 2019 harvest. All-trans-β-carotene represented 12.20 ± 46 to 25.81 ± 35 g / 100g of sample in the 2018 harvest, and 8,51 ± 11 to 25.23 ± 28 g / 100g of sample in the 2019 harvest. The characterization of monomeric anthocyanins showed the presence of 3-glucoside and 3.5-diglucosides of four aglycone and totaled 3558 ± 36 to 2822 ± 30g C3G / 100g of sample in the 2018 harvest, and 20443 ± 45 to 2863 ± 31 g C3G / 100g of sample in the 2019 harvest. Antioxidant activity was determined by monitoring the effect of fluorescence decay on the hydrophilic extract by deactivating the peroxyl radical (ROO), generated by term decomposition of AAPH at 37 ºC that resulted in the value 94.4-97.2 µmol TE / g. We also found 461 ± 26 mg GAE / 100 g in the 2018 harvest and 323 ± 34 mg GAE / 100 g in the 2019 harvest for total phenolic compounds. Thus, this study concluded that there was a decrease in the size of whole fruits in the 2019 harvest when compared to 2018, and significant quantitative differences in the contents of the compounds between the samples analyzed and between the two crops. However, the nutritional characteristics and the main bioactive compounds remained present in both samples and crops. We also conclude that the characteristics presented here are attributes that arouse the interest of further studies on the potential of regional fruits such as jambolão in Santos, to the point of overcoming the paradigm of its waste and leading it to the table of family consumption and industrial use.